Country Partnership Framework for the Republic of Rwanda for the Period of FY21-FY26 - World Bank Group (World Bank, Washington, DC, 2020)
This Country Partnership Framework  (CPF) sets out the World Bank Group’s plans  for addressing the country’s development priorities as identified in the 2019 Systematic Country Diagnostic (SCD) and Rwanda’s  National  Strategy  for  Transformation as well  as  supporting  Rwanda’s response  to  the  COVID‐19  pandemic  to  recover  from  the  negative  public  health  and  socio‐economic impacts of the pandemic.